Balloon Dilatation of Esophageal Strictures in Children With Bullous Epidermolysis: Description of Case Series - A. V. Tupylenko; M. M. Lohmatov; N. N. Murashkin; E. Y. Dyakonova; I. V. Filinov; S. A. Maksimova; R. V. Epishev; I. A. Surkova; T. N. Budkina; V. I. Oldakovsky (Педиатрическая фармакология)
Esophageal strictures are the most common complications of bullous epidermolysis in children. Strictures cause the development of dysphagia that prevents oral alimentation and receipt of an adequate amount of nutrients that is accompanied by a violation of nutritional status, weight loss, and delayed physical development of a child. Disturbed swallowing can also cause aspiration syndrome, pneumonia, and airway obstruction. To eliminate dysphagia and reduce the risk of complications, it is necessary to restore esophageal patency. The article describes the results of X-ray with assisted balloon dilatation in 19 children with bullous epidermolysis and dysphagia. It is shown that this method of esophagus recanalization allows to effectively and safely restore oral alimentation of children already in the first day after intervention with a gradual expansion of the diet.